Pelinggih Pajenengan as a Manifestation of Śiwa-Buddha Syncretism in the Pegulingan Temple Gianyar Bali - Saitya, Ida Bagus Subrahmaniam; Arimbawa, I Komang Suastika; Jagadhita, Pande Putu Puja (Jayapangus Press, 2023)
The teachings of Śiwa who dominate and are recognized as a majority and even animates most of the Hindu values in Bali do not forget to accommodate and harmonize themselves with other teachings, one of which is the Buddhist. From this, the existence of Buddhist teachings is still developing today. The reflection of the unification of the value of Śiwa-Buddha's teachings, one of which can be found at the Pura Pegulingan in Manukaya Village. The manifestation of the Śiwa-Buddha syncretism in the Pegulungan Temple is the Pajenengan Temple. Pajenengan's Pelinggih itself is a Pelinggih in the form of a Buddhist stupa which is worshiped jointly by Hindus and Buddhists who are the patrons of the temple. The influence of Buddhism in the Tampaksiring and Pejeng areas was inseparable from the policies of Masula Masuli in Bali in the śaka year 1100 (1178 AD). In particular, this study aims to analyze the Pelinggih Pajenengan as a form of Śiwa -Buddha syncretism at Pegulungan Temple. In particular, this study aims to analyze the Pelinggih Pajenengan as a form of Śiwa-Buddha syncretism at Pegulingan Temple. This research is qualitative research with a theological approach, while the data collection techniques used include observation, interviews, literature study, and document study. This research is qualitative research with a theological approach. The results of this study are very important because it shows the intense Pelinggih as a form of syncretism Śiwa-Buddha. Pelinggih Pajenengan was also called Padma Asta Dala in a Buddhist statue of gold with a standing attitude or Tribangga with the attitude of the waramudra hands. Thus, the existence of Pelinggih Pajenengan which contains the patterns of Śiwa and Buddha. The discovery of relief of stupa and lingga-yoni is proof that the unification of the two different teachings is very possible and as a unifying medium for Hindus and also Buddhism in the Pegulingan temple. In addition, the mantra addressed to Śiwa Raditya was also spoken by Śiwa-Buddha Raditya, this proves that the teachings of Śiwa-Buddha have been integrated in the Pegulingan temple.